Legal Protection Of Savings And Loan Cooperatives Against Cooperative Members Committing Default - Rochman, Auliya; Naridha, Alifah Nur Fitriana; Banjarnahor, David; Prayudha, Tengku Andrias; Ikhsan, Sy. Muhammad (JURNAL HUKUM SEHASEN, 2025)
This study explores Savings and Loan Cooperatives' legal protection in dealing with cooperative member defaults and the legal basis for resolving default issues between cooperatives and their members in compliance with existing law. The research method utilised to analyse these issues is normative legal research utilising statutory and conceptual approaches. Our legal material collection method is a literature study. Analysis of legal materials is deductive. A main premise is needed for deductive reasoning. Next, a small premise. Two premises lead to a conclusion. As a result of the research, the Savings and Loan Cooperative cannot be separated from a binding agreement between the Savings and Loan Cooperative and its members in providing credit.where the preparation of the agreement must be clear and firm including the rights and obligations of both parties in detail, including the terms of loan repayment in the content of the clause of the agreement This is very important to prevent default and protect the interests of the Savings and Loan Cooperative and its members. Where as a basis, Article 1320 of the Civil Code and Article 1338 paragraph 1 of the Civil Code are further explained in 1321 of the Civil Code and Article 1243 of the Civil Code, where basically the Savings and Loan Cooperative uses anticipatory measures to ensure that the agreement between the Savings and Loan Cooperative and its members is made legally and without elements of legal defect in order to minimize the occurrence of default. For repressive measures of the Savings and Loan Cooperative (KSP) in Dealing with Cases of Default of Its Members, it can be explained in Articles 1239 of the Civil Code and 1243 of the Civil Code, which are further explained in Articles 1244, 1246 and 1247 of the Civil Code, the settlement of default disputes between Savings and Loan Cooperatives and their members is regulated in Articles 1234, Article 1313, Article 1238, Article 1236 and Article 1266 of the Civil Code which explain that in essence Savings and Loan Cooperatives have certainty law in.